1999
DOI: 10.1111/j.1559-1816.1999.tb02025.x
|View full text |Cite
|
Sign up to set email alerts
|

Gangsta’ Rap and a Murder in Bakersfield1

Abstract: The present study explores the biasing effects of gangsta' rap lyrics on subject perceptions of a murder trial defendant's personality. The lyrics were those actually authored by a defendant in a murder trial on which the present author was a psychological consultant for the defense. Results strongly indicate that the defendant was seen as more likely to have committed a murder than had he not been presented as authoring such lyrics. Surprisingly, results also show that the writing of such rap lyrics was more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…Another study provides some support for Fischoff's (1999) hypothesis that race or ethnicity plays a role in how people respond to rap lyrics. Social psychologist Carrie B.…”
Section: ''Some Wish To Destroy This Scene Called Hip-hop'' 3 : the Rmentioning
confidence: 91%
“…Another study provides some support for Fischoff's (1999) hypothesis that race or ethnicity plays a role in how people respond to rap lyrics. Social psychologist Carrie B.…”
Section: ''Some Wish To Destroy This Scene Called Hip-hop'' 3 : the Rmentioning
confidence: 91%
“…Stereotypes associating rap music with dangerousness do not, however, only affect evaluations of lyrics. Prior studies also find that stereotypes about rap music inform impressions of the people who write the music (Dunbar & Kubrin, 2018;Fischoff, 1999). For example, Fischoff (1999) found that people make negative judgments about a person from the mere fact that the person writes violent rap lyrics.…”
Section: Anti-black Attitudes In Disguisementioning
confidence: 99%
“…Prior studies also find that stereotypes about rap music inform impressions of the people who write the music (Dunbar & Kubrin, 2018;Fischoff, 1999). For example, Fischoff (1999) found that people make negative judgments about a person from the mere fact that the person writes violent rap lyrics. In his study, participants were presented with biographical information about an African-American male high school senior who has a good academic record, is on the track team, and plans to attend college on an athletic scholarship.…”
Section: Anti-black Attitudes In Disguisementioning
confidence: 99%
See 2 more Smart Citations